Van Gogh in Provence and Auvers - Welsh-Ovcharov, Bogomila (New York : Universe Pub., 2008)
Examines the life and work of Dutch artist Vincent van Gogh during his last two years, from February, 1888 when he moved to the south of France, to his suicide in July, 1890; and includes reproductions of his paintings and drawings produced in Arles, the asylum at Saint-Remy-de-Mausole, and in Auvers.
Includes index.
Adult
Keywords: Gogh, Vincent van, -- 1853-1890.; Gogh, Vincent van, -- 1853-1890.; Painting, French; French painting